The Executory Authority of Constitutional Court Decisions in the 2024 Local Head Election - Yulida, Devi; Talisa, Rina (Acta Law Journal, 2024)
Indonesia views Local Head Elections as a vital expression of people's sovereignty in its democratic system. The Constitutional Court ensures the fairness of democracy through rulings on these elections. This study examines the executory authority of the Constitutional Court's decisions regarding Local Head Elections in 2024, focusing on Decisions No. 60/PUU-XXII/2024, 70/PUU-XXII/2024, and 126/PUU-XXII/2024. Using a normative legal approach, the research analyzes laws and concepts related to these elections, with data qualitatively analyzed and presented narratively. The findings highlight that the Constitutional Court’s final and binding decisions enhance legal certainty and improve the electoral system, thereby strengthening Indonesia’s democracy. These rulings take immediate effect without requiring an executive body and must be respected by all state institutions, reflecting the principle of checks and balances in governance. Effective implementation requires cooperation among state institutions, with the legislative and executive branches expected to follow up on the rulings through lawmaking. The General Election Commission plays a critical role in organizing elections based on these laws. As a rule-of-law state, adherence to the law by all institutions is essential to achieving a just and improved democratic system.